Cassava Chips Production System in Max-Plus Algebra - Ira Wulan Sari; Fanny Adibah; Sri Rejeki Puri Wahyu Pramesthi (Universitas Islam Lamongan, 2023)
The research discussed here relates to the cassava chips production system. The production system was analyzed using petri net and algebra of maxplus. The goal is to obtain information on the completion time for each process and to know the estimated time of completion of production each day. Based on the data obtained, it can be described the flow of the production process and then formed a graph so that it can be formed a petri net using the Woped 3.1.0 tool. From the results of the petri net then analyzed and can be built coverability tree. So that, the completion time for each process and the estimated time for completion of production each day can be known.